2015
DOI: 10.3390/molecules20010519
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Animal and Plant Lectins with Antimicrobial Activities

Abstract: Abstract:Lectins are multivalent proteins with the ability to recognize and bind diverse carbohydrate structures. The glyco -binding and diverse molecular structures observed in these protein classes make them a large and heterogeneous group with a wide range of biological activities in microorganisms, animals and plants. Lectins from plants and animals are commonly used in direct defense against pathogens and in immune regulation. This review focuses on sources of animal and plant lectins, describing their fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 186 publications
0
48
0
6
Order By: Relevance
“…In addition, pCramoll did not present antimicrobial action against C. gatti , an activity rarely found in the legume lectin domain (Dias et al, 2015). However, a few studies have shown the immunomodulatory potential of plant lectins to combat bacterial and fungal infections (Alegre-Maller et al, 2014), in this context pCramoll influences the inflammatory responses against C. gatti .…”
Section: Discussionmentioning
confidence: 94%
“…In addition, pCramoll did not present antimicrobial action against C. gatti , an activity rarely found in the legume lectin domain (Dias et al, 2015). However, a few studies have shown the immunomodulatory potential of plant lectins to combat bacterial and fungal infections (Alegre-Maller et al, 2014), in this context pCramoll influences the inflammatory responses against C. gatti .…”
Section: Discussionmentioning
confidence: 94%
“…; Dias et al . ). Several studies have reported that these proteins are able to affect bacterial growth and viability as well as to disrupt the bacterial intracellular signaling (quorum sensing) involved in the formation of biofilms (Islam et al .…”
Section: Introductionmentioning
confidence: 97%
“…Lectins are carbohydrate-binding proteins widely distributed in plants (Saha et al 2014). The interactions between lectins and sugars play important roles in several biological processes and mediate a broad range of biological activities, including antibacterial and antibiofilm activities (Klafke et al 2013;Dias et al 2015). Several studies have reported that these proteins are able to affect bacterial growth and viability as well as to disrupt the bacterial intracellular signaling (quorum sensing) involved in the formation of biofilms (Islam et al 2009;Cavalcante et al 2013;Saha et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has become clear that lectins play two major roles in plants. First, they are deposits of proteins that can be boosted for the growth and development of plants, and secondly, in the defense of plants against herbivores and pathogens (Barre et al, 2002;Vandenborre et al, 2011;Dias et al, 2015;Troegeler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%